Competing ontologies: A primer for public administration - Stout, Margaret (2012)
A growing number of public administration theorists are taking up the question of ontology-the nature of existence. This primer on the topic provides a basic explanation of ontology, describes the fundamental debates in the competing ontologies of Western philosophy, and discusses why ontology is important to social and political theory, as well as to public administration theory and practice. Using an ideal-type approach, the author analyzes how different ontologies imply particular political forms that undergird public administration theories and practices. This ideal-type model can be used to identify the ontological assumptions in these theories and practices. The article concludes with an invitation for personal reflection on the part of scholars and practitioners in regard to which ontology best fits their experience and belief and the alternatives that we might pursue for a better future. - Reproduced.
Keywords: Public administration